2011
DOI: 10.1007/s11270-011-1041-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hydraulic and Organic Loadings on the Performance of a Full-Scale Facultative Pond in a Temperate Climate Region (Argentine Patagonia)

Abstract: This work focuses on the performance of a primary facultative pond, in a full-scale waste stabilization pond system, located in a temperate climate region (average air temperature in winter, 7.7°C; spring and autumn, 14.0°C; and summer, 19.9°C) in Puerto Madryn city-Argentine Patagonia (42°45′S; 65°05′W). Experimental work was conducted for 43 months in seven sampling points. During the experimental time frame, the influent flow rate increased from 12,000 to 15,500 m 3 /day; the surface organic loading ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 26 publications
0
28
1
Order By: Relevance
“…While this text studies the aforementioned as the most frequent parameters, other parameters may have an effect on an oxidation pond's performance, such as flow rate (Kirby et al 2009;Faleschini et al 2012), volume (Fyfe et al 2007), and area (Craggs et al 2003). However, there are still other parameters that can be considered, but the previously mentioned have been surveyed as having the most effect on the overall treatment of wastewater within oxidation ponds.…”
Section: Design Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this text studies the aforementioned as the most frequent parameters, other parameters may have an effect on an oxidation pond's performance, such as flow rate (Kirby et al 2009;Faleschini et al 2012), volume (Fyfe et al 2007), and area (Craggs et al 2003). However, there are still other parameters that can be considered, but the previously mentioned have been surveyed as having the most effect on the overall treatment of wastewater within oxidation ponds.…”
Section: Design Factorsmentioning
confidence: 99%
“…The BOD removal efficiency is dependent on numerous factors and can vary from approximately 81 % (Yeh et al 2010), 50 % (Craggs et al 2003), 50.3 % (Meneses et al 2005), and others (Banerjee and Sarker 1997;Faleschini et al 2012;Mtethiwa et al 2008;Sukias et al 2001;Tanner and Sukias 2003;Abbasi and Abbasi 2010). The BOD removal is not only dependent on the type of oxidation pond, but on other factors such as the environment (Mara and Pearson 1998).…”
Section: Organicsmentioning
confidence: 99%
“…No nitrate was detected in Pond 1 and it is therefore unlikely that any ammonia oxidation took place. Ammonia could also have been lost through volatilisation, although during this period the pH of the pond was near neutral: recent studies have shown however that a number of factors are involved in ammonia removal and their interrelations are complex (Yamamoto et al, 2010;Faleschini et al, 2012). Ammonia in Pond 2 remained low (average 0.4 mg l -1 ) until about 10 August when the increasing nitrogen load in Pond 1 began to break through.…”
Section: Cod and Bodmentioning
confidence: 99%
“…During operation, however, an unexpected shock load modified the research direction to include consideration of recovery strategies based on laboratory-scale testing. To date there have been few studies on the impact of shock loadings on these systems, but recent studies are indicating the importance of loading rates in temperate climate systems (Abis and Mara, 2005;Faleschini et al, 2012) MATERIALS AND METHODS WSP layout and operation. Figure 1 shows the system layout.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, WWT HRAPs are much more efficient than the conventional waste stabilization ponds (WSP) used to treat the wastewater of small to medium-sized communities world-over. WWT HRAPs can achieve much more efficient nutrient removal than WSPs in shorter time, 4-8 days compared with 30 -60 days (Faleschini et al, 2012 andCraggs, 2011). In addition, since WSPs are unmixed, only unicellular, motile or buoyant algal genera including Chlorella, Chlamydomonas and Anabaena, tend to grow in them (Pearson, 2005).…”
Section: Introductionmentioning
confidence: 99%